Analisis Prinsip-Prinsip Good Governance Pada Satuan Pelaksana Perhubungan Kecamatan Cempaka Putih (Studi Kasus Pengelolaan Parkir Di Kelurahan Cempaka Putih Timur) - Fianda Syaidinar; Tri Ubayanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of this research is to identify the good governance principles at the Transportation Implementation Unit of Cempaka Putih subdistrict, case study of parking management in East Cempaka Putih Village. This research uses qualitative descriptive analysis method to describe and explain in detail the existing phenomena by using interview as supporting instrument. The result of this research shows that the good governance principles at the Transportation Implementation Unit of Cempaka Putih subdistrict have not been well implemented. The obstacle includes the lack of competent human resource. The efforts which can be made include improving competence of the existing human resource, adding personnel, and expanding parking lot.